Controlling the quantum world of atoms, molecules, and photons : an interim report (National Academies Press, 2005)
As part of its Physics 2010 decadal survey, the NRC has undertaken a study of opportunities in atomic, molecular, and optical (AMO) science and technology over roughly the next decade. This study has been requested by the Department of Energy and the National Science Foundation. They asked the NRC to assess the state of AMO science, emphasizing recent accomplishments and identifying new and compelling scientific questions. A final report on this study is expected in the summer 2006. This interim report provides a preview of the final document. It presents a summary of the key opportunities in forefront AMO science and in closely related technologies, and a discussion of some of the broad-scale conclusions of the final report. The interim report also describes how AMO science supports national R & D priorities.